Covid-19 and Mental Health: The Growing Need of Telecounseling in Indonesia - Edilburga Wulan Saptandari (Buletin Psikologi, 2020)
Covid-19 pandemic has not only threatened public physical health but also mental health. The mental health effects of this pandemic can include anxiety of contamination and death as well as feelings of isolation. Counseling has been proved as an effective method of supporting the physical and psychosocial needs of the individual affected. Technological advancement makes it possible for psychologists and clients to carry out counseling sessions without the needs of physical presence in one place by utilizing various modes of telecommunication. This form of counseling is known as telecounseling. As a relatively new form of counseling in Indonesia, numerous aspects need to be considered in implementing telecounseling. This article aims to explore the considerations taken in conducting telecounseling sessions in Indonesia. Their opportunities and challenges which might not be present in an offline face-to face counseling will also be discussed. Psychologists need to develop both practical and technical competencies to be able to provide adequate telecounseling services. Suggestions for development are also given to other relevant parties such as psychological service institutions, professional associations, and education providers.